2004
DOI: 10.1021/la049103b
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Alkanethiol Self-Assembled Monolayer Adsorption on Sputtered Gold Substrates

Abstract: A detailed study of the self-assembly and coverage by 1-nonanethiol of sputtered Au surfaces using molecular resolution atomic force microscopy (AFM) and scanning tunneling microscopy (STM) is presented. The monolayer self-assembles on a smooth Au surface composed predominantly of {111} oriented grains. The domains of the alkanethiol monolayer are observed with sizes typically of 5−25 nm, and multiple molecular domains can exist within one Au grain. STM imaging shows that the (4 × 2) superlattice structure is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 50 publications
(124 reference statements)
3
77
0
2
Order By: Relevance
“…Details on specific conditions and preparations for accurate imaging of adsorbed alkanethiolates can be found in Ref. 30. The chemical composition of the samples was determined using a SISONS model EA-1108 analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Details on specific conditions and preparations for accurate imaging of adsorbed alkanethiolates can be found in Ref. 30. The chemical composition of the samples was determined using a SISONS model EA-1108 analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…The 150 nm size of {111} grains on Au:1 surfaces is ≃ 3 times greater than the SAM film thickness, and suggests single-crystal epitaxial growth. Some monatomic depressions exist on the surface of each grain prior to treatment in the alkanethiol solution, but we have recently demonstrated that the alkanethiol covers the surface and depressions alike [26,31]. Thus sputtered Au films produce good quality substrates for alkanethiol-based resist adsorption for atomic nanolithography applications.…”
Section: Crystal Orientation and Grain Densitymentioning
confidence: 99%
“…This resolution issue was addressed by Love et al [25] who reported that Pd substrates yielded better post-etch resolution than their Au counterparts when coated with alkanethiol monolayers for nanolithographic purposes. We have recently reported [26] that a resolution limit of ≃ 20 nm is found when 1-nonanethiol SAMs are adsorbed on sputtered Au substrates. The results indicated that the quality of the Au surface is paramount in realizing a low defect-density molecular monolayer.…”
Section: B Alkanethiol Self-assembled Monolayers On Aumentioning
confidence: 99%
See 1 more Smart Citation
“…Each sandwich is composed of two hexagonal planes of S atoms and an intermediate hexagonal plane of Mo atoms, trigonal prismatically coordinated to the S atoms. It is important to point out that at low bias, constant current STM images reflect the local density of states at the Fermi level projected to the position of the tip apex [10,11]. In general, the images represent a convolution of the geometric and electronic structure of the surface.…”
Section: Structural Characterisation Of Compressed Mosmentioning
confidence: 99%